The Importance of Kashkadarya Region in the Development of Pilgrimage Tourism - Ergasheva Yulduz Alimovna; Eralov Azamat Jomurodovich (Genius Publishing Group, 2022)
This article talks about the importance of kashkadarya region in the development of pilgrimage tourism. The author, relying on archaeological data, archival documents and written sources, analyzed the problem on the basis of existing scientific and historical literature and studied the peculiarities of kashkadarya region in the development of Tourism. In addition, the article provides information about the activities of our research government in the field of Tourism.
Keywords: Tourism; tourists; infrastructure; shrines